2016
DOI: 10.1111/1475-6773.12469
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Dental Care and Long‐Term Dental Outcomes among ALL Kids Enrollees

Abstract: Whether PDVs without sealants actually reduce restorative/emergency pediatric dental services is questionable. Further research into benefits of PDV is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Despite early reports suggesting that dental caries–related expenditures are less among children who use POHS (Pahel et al 2011; Beil et al 2012; Sen et al 2013; Achembong et al 2014; Sen et al 2016), our results are consistent with more recent data (Blackburn et al 2017). Our results show that non-GA dental expenditures are similar over an 8-y follow-up regardless of whether children used POHS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Despite early reports suggesting that dental caries–related expenditures are less among children who use POHS (Pahel et al 2011; Beil et al 2012; Sen et al 2013; Achembong et al 2014; Sen et al 2016), our results are consistent with more recent data (Blackburn et al 2017). Our results show that non-GA dental expenditures are similar over an 8-y follow-up regardless of whether children used POHS.…”
Section: Discussionsupporting
confidence: 86%
“…An opportunity exists to explore the impact of POHS on dental GA utilization and expenditures. While some authors have examined caries-related treatment differences between children who received POHS and those who did not (Beil et al 2012; Sen et al 2013; Sen et al 2016), no evaluation compares the use of GA for dental treatment between these groups. The purpose of this article is to begin to assess whether POHS may influence dental GA utilization among Medicaid-enrolled children in North Carolina.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,58,59,60 Sen et al reported that among Medicaid-enrolled children under age 3, preventive dental visits without sealant placement were associated with increased NTDC ED use. 32…”
Section: Other Enabling Factorsmentioning
confidence: 99%
“…There is considerable heterogeneity within the literature in the methods used for analyzing ED use for NTDCs. Some studies have examined primary data, 14,27,28,29,30 discharge records, 31 claims data, 13,17,32 or self-reported surveys. 33,34 Regarding study setting, studies have analyzed data from local, state, or nation-wide electronic databases, raising questions about generalizability of the findings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although reimbursement may affect getting children to the dental office, it may not influence services received there and may differentially benefit the oldest children rather than the youngest (13). In response to a 2004 US Supreme Court decision that required Texas's Medicaid program to comply with guidelines on increasing access to dental care providers (14), Texas increased the amount of fees reimbursed for dental preventive care by 52.5% on September 1, 2007. Although increasing access to preventive dental care is important, preventive care alone does not reduce the likelihood of needing tertiary oral health services (caries-related surgery, sedation, and ED visits) (15). Previous research established that Medicaid reimbursements for preventive dental care substantially increased selfreported preventive dental visits in several states (11).…”
Section: Introductionmentioning
confidence: 99%